2017
DOI: 10.3352/jeehp.2017.14.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of practical training on the learning motivation profile of Japanese pharmacy students using structural equation modeling

Abstract: PurposeTo establish a model of Japanese pharmacy students’ learning motivation profile and investigate the effects of pharmaceutical practical training programs on their learning motivation.MethodsThe Science Motivation Questionnaire II was administered to pharmacy students in their 4th (before practical training), 5th (before practical training at clinical sites), and 6th (after all practical training) years of study at Josai International University in April, 2016. Factor analysis and multiple-group structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Incorporating practical sessions in pharmacology and pharmacotherapy might have positive effects on the knowledge, attitudes, and skills of pharmacists [ 13 ]. Recently, it has been reported that practical training programs increased learning motivation among pharmacy students [ 14 ]. Similarly, using computer simulations was shown to enhance knowledge of medications and pharmacology [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating practical sessions in pharmacology and pharmacotherapy might have positive effects on the knowledge, attitudes, and skills of pharmacists [ 13 ]. Recently, it has been reported that practical training programs increased learning motivation among pharmacy students [ 14 ]. Similarly, using computer simulations was shown to enhance knowledge of medications and pharmacology [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently accessed article was “Reliability of a viva assessment of clinical reasoning in an Australian pre-professional osteopathy program assessed using generalizability theory” by Vaughan et al [ 1 ], which was published in January this year (accessed 11,913 times). The next most-viewed article was “Effect of practical training on the learning motivation profile of Japanese pharmacy students using structural equation modeling” by Yamamura and Takehira [ 2 ], which was published this February (accessed 11,339 times). This article was also the most downloaded article in 2017 (downloaded 223 times), and has already been cited by another article.…”
mentioning
confidence: 99%
“…The authors were given permission to use the questionnaire for this study. The average score and standard deviation for each item and each school year among the students were expressed in a previous paper [ 2 ]. The students’ learning process was measured with the 20-item “revised two factor study process questionnaire (R-SPQ-2F)” [ 12 ], which was translated into Japanese.…”
Section: Methodsmentioning
confidence: 99%
“…As pharmacy education lasts 6 years, students must maintain strong motivation. In previous research, the authors noted a positive change in learning motivation based on self-determination and an inclination towards “deep learning” among students after the introduction of clinical clerkships [ 2 , 3 ]. The students were considered to be motivated during clinical clerkship and to understand the underlying concepts of pharmacy by deep learning [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation